Principal's Leadership In Developing Teacher Competence In Special Schools (SLB) C Muzdalifah - Sugiarjo Sugiarjo; Mhd. Habibu Rahman; Danny Abrianto (CV. Generasi Insan Rafflesia, 2026)
This study aims to analyze the principal's leadership in developing teacher competency at Muzdalifah Special Needs School (SLB C) in Medan and to identify supporting and inhibiting factors in this process. This study used a descriptive qualitative approach. Subjects included the principal and teachers of SLB C Muzdalifah. Data collection techniques included in-depth interviews, observation, and documentation. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques.The results indicate that the principal implements democratic and visionary leadership, manifested through two-way communication, ongoing academic supervision, motivation, and participatory decision-making. This leadership contributes significantly to improving the pedagogical, professional, social, and personal competencies of teachers in serving students with special needs. Supporting factors for principal leadership include high leadership commitment, a collaborative work culture, teacher participation, and external training and partnerships. Inhibiting factors include budget constraints, uneven educational qualifications for SLB teachers, and the complex characteristics of students with special needs. This study confirms that participatory principal leadership and a focus on professional development play a crucial role in improving teacher quality and educational services in special needs schools.